COST-EFFECTIVENESS DEXKETOPROFEN VS KETOROLAC IN CAESAREAN PATIENTS AT 'X' HOSPITAL, PANDEGLANG - Yusransyah, Yusransyah; Sofi Nurmay, Stiani; Farahdina, Chairani; Latifah Nur, Rizki; Baha, Udin (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2025)
Post-cesarean section pain must be treated promptly and appropriately to prevent chronic conditions. Dexketoprofen and Ketorolac are non-narcotic analgesics commonly used to manage such pain. This study aimed to analyse the cost-effectiveness of dexketoprofen and ketorolac in patients undergoing cesarean sections at Mother and Child Hospital